The Dutch national kilometre charge: Impacts on the Dutch car market and environment - Karst Geurs; Rinus Haaijer; Hendrik J. Meurs (European Regional Science Association (ERSA), 2010)
The Dutch government has decided to gradually introduce a complex national road pricing system in the years 2012 to 2018. Existing car purchase taxes and the annual road taxes are to be replaced by a kilometre-based charging system. Several appraisal studies have been conducted to examine the impacts of different pricing variants, using the well-known Dutch national model system (NMS) and the national car market model DYNAMO. The car market model has recently been developed and simulates yearly car ownership and car purchase behaviour of households at a detailed level (120 car types * 70 household types), and endogenously models second hand car prices as a pricing mechanism to create an equilibrium in supply and demand. The Dutch road pricing scheme is expected to have major impacts: car ownership is projected to increase by 5-6% in the long run, car use is to reduced by by 10-15% and congestion on the main motorway network in 2020 by about 50%, compared to a reference scenario. Cost-benefit analysis studies, using output from the transport models, show significant positive welfare effects. This paper will review existing appraisal studies on the impacts of the kilometre charge, and describe the Dutch car market model DYNAMO and projections of the impacts of different CO2 pricing schemes. Results from DYNAMO estimations show that abolishing existing car purchase and road taxes by a CO2 differentiated kilometre charge has unintended consequences in the form of rising car ownership and increasing shares of diesel cars and relatively large and heavy vehicle types. Explanations for these unintended effects are that households react more to present one-off fixed costs than to recurrent variable costs, and total car costs are reduced for households with relatively low car mileages. For households with low car usage, the reduction of fixed car taxes is not fully compensated by increases in variable costs, and savings can be used to buy a more expensive and larger car. However, overall environmental impacts of CO2 differentiated kilometre charges are quite positive resulting from the reduction in car travel.
Keywords: 330